Effect of ascorbic acid assisted dilute acid pretreatment on lignin removal and enzyme digestibility of agricultural residues. (January 2021) - Sheng, Yequan; Tan, Xin; Gu, Yuanjie; Zhou, Xin; Tu, Maobing; Xu, Yong
Abstract: Efficient pretreatment for lignocellulosic biomass is crucial in developing a viable biorefinery process. An ascorbic acid (AsA)-assisted dilute acid pretreatment strategy was developed to improve enzymatic hydrolysis efficiency. In this study, the effect of ascorbic acid addition on the dilute acid pretreatment of wheat straw (WS), corn stover (CS), and corncob (CC) was assessed and compared. The 72 h hydrolysis yield was improved by 12.47, 18.78, and 13.57% in dilute acid pretreated WS, CS, and CC with ascorbic acid addition, respectively. In addition, the cellulose accessibility, enzyme adsorption, chemical composition analysis, and structural features of pretreated biomass with ascorbic acid were determined to better understand its mechanistic effect on enzymatic hydrolysis. The results indicated that the addition of ascorbic acid in the dilute acid pretreatment reduced surface lignin content and enhanced cellulose accessibility, delignification ratio, and enzyme adsorption ability. Highlights: The addition of ascorbic acid improved enzymatic hydrolysis. The addition of ascorbic acid increased delignification ratio of pretreated substrates. The addition of ascorbic acid resulted in better cellulose accessibility and enzyme adsorption.